Between-day reliability of trunk orientation measured with smartphone sensors during sit-to-stand in asymptomatic individuals. (February 2023) - Gordon, Shaylah; Kind, Oliver; Singh, Gurpal; Wood, Alexandra; Gallina, Alessio
Abstract: Background: Trunk kinematics during sit-to-stand is often impaired in individuals with musculoskeletal disorders. Trunk kinematics is commonly assessed in laboratories using motion capture; however, this equipment is often not available outside research centers. Smartphones are widely available and may be a suitable alternative to assess trunk orientation during sit-to-stand remotely. Objectives: We investigated whether trunk orientation in the sagittal plane during sit-to-stand can be measured reliably between days when collected remotely using smartphones. Design: Cross-sectional study. Method: Forty-three asymptomatic participants performed 15 sit-to-stand movements in two separate sessions remotely over videoconferencing. Trunk orientation was measured using each participant's smartphone. Absolute peak trunk orientation in the sagittal plane was extracted during standing, sitting, stand up and sit down. Relative trunk orientation was calculated as the difference between sitting and stand up, or sitting and sit down. Reliability was assessed using Intraclass Correlation Coefficient (ICC2, k ), Standard Error of Measurement (SEM) and Minimal Detectable change (MDC). Between day bias and between-gender differences were assessed using T tests. Results: All measures showed good reliability (ICC2, k > 0.80; SEM < 5.6°; MDC < 13.6°) and no between-day bias (p > 0.31). Relative measures were more consistent (ICC2, k > 0.88; SEM < 3.6°; MDC < 9.9°). No between-gender differences were observed for relative orientation (p > 0.75). Conclusions: Sagittal trunk orientation during sitting, standing, and sit-to-stand can be measured reliably when asymptomatic individuals use their own smartphones supervised over videoconferencing. These findings support the use of smartphone sensors for assessing how trunk orientation changes over time, which may assist physiotherapists assess movement patterns of individuals with musculoskeletal disorders remotely. Highlights: Smartphone sensors provide reliable trunk orientation estimates between days. Reliability was higher for sit-to-stand range of motion than sitting or standing. Smartphone sensors may be helpful to monitor trunk orientation over time remotely.